2023
DOI: 10.3390/bioengineering10080894
|View full text |Cite
|
Sign up to set email alerts
|

Automated Segmentation of Levator Ani Muscle from 3D Endovaginal Ultrasound Images

Nada Rabbat,
Amad Qureshi,
Ko-Tsung Hsu
et al.

Abstract: Levator ani muscle (LAM) avulsion is a common complication of vaginal childbirth and is linked to several pelvic floor disorders. Diagnosing and treating these conditions require imaging of the pelvic floor and examination of the obtained images, which is a time-consuming process subjected to operator variability. In our study, we proposed using deep learning (DL) to automate the segmentation of the LAM from 3D endovaginal ultrasound images (EVUS) to improve diagnostic accuracy and efficiency. Over one thousan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Studies that examined the hiatus area of the elevator using DL reported DSIs greater than 0.9 [4,5,15,16], establishing a value of 0.94 in the case of the urogenital hiatus [17]. However, when using the DL to study solid structures, as in the case of the levator ani muscle, the DSI is lower, ranging between 0.6 and 0.77 [4,18,19]. The reason for this may be that solid structures present less contrast with neighboring structures and are more difficult to delimit.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that examined the hiatus area of the elevator using DL reported DSIs greater than 0.9 [4,5,15,16], establishing a value of 0.94 in the case of the urogenital hiatus [17]. However, when using the DL to study solid structures, as in the case of the levator ani muscle, the DSI is lower, ranging between 0.6 and 0.77 [4,18,19]. The reason for this may be that solid structures present less contrast with neighboring structures and are more difficult to delimit.…”
Section: Discussionmentioning
confidence: 99%